Novel Method For The Detection Of HIV Using RP 24 Recombinant Protein From E. Coli BL-21 - S. C. SINGH; M. VASUDEVAN; RICHA; R. P. SINHA (International Journal of Pharma and Bio Sciences, 2010)
A novel method for the purification of recombinant protein 24 (rp24) of human immunodeficiency virus type 1 (HIV- 1) from Escherichia coli is described. The protein was over-expressed in E. coli (BL21 lDE3) cells to the levels of 30 % total cell protein in the soluble fraction. The recombinant protein was extracted and purified to near homogeneity by ion-exchange steps followed by ultrafiltration. The recombinant protein in combination with synthetic peptides from immuno-dominant stretches derived from the ‘envelope’ proteins of HIV-1 and HIV-2 was used for the development of an ELISA kit, for detection of antibodies against the virus in human serum and/or plasma.